Prospective Strategic Planning: MACTOR and SMIC Methods (Dimensión Empresarial, 2019)
The authors, Quintero and Hamann, express their extensive knowledge about strategic planning and prospective throughout the text. Also, this work highlights the experience in university teaching in the broad field of administration, since the book starts from a pedagogical premise and has a high recreational value. As for its composition, it consists of five chapters. In these, a referential framework is presented, the instructions for applying the MACTOR and SMIC methods, the modeling of macro environments and individualized organizations, the process of prospective analysis in social or organizational spectra and the implementation of prospective analysis as a business plan for a company. In addition, an annex with 19 formats is attached to develop data collection tools that facilitate the achievement of a study based on the French prospective school.